2023
DOI: 10.1096/fj.202301182r
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the primocolonizing microbiota alters epithelial homeostasis and imprints stem cells in the colon of neonatal piglets

Martin Beaumont,
Corinne Lencina,
Katia Fève
et al.

Abstract: The gut microbiota plays a key role in the postnatal development of the intestinal epithelium. However, the bacterial members of the primocolonizing microbiota driving these effects are not fully identified and the mechanisms underlying their long‐term influence on epithelial homeostasis remain poorly described. Here, we used a model of newborn piglets treated during the first week of life with the antibiotic colistin in order to deplete specific gram‐negative bacteria that are transiently dominant in the neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Beside weaning, the neonatal period (from birth to post-natal day 28 in pigs), is also a key period in terms of intestinal development, with changes in epithelium morphology and gene expression with post-natal age [13], as well as ISC dynamics depending on gut location [14]. As opposed to weaning where the luminal environment does not seem to impact ISC, we recently demonstrated that changes in the luminal environment composition during the first week of life can imprint ISC, since organoids derived from the colon of antibiotic-treated vs. vehicle-treated piglets retained some, but not all, features of the changes observed in vivo at the epithelial level [15].…”
Section: Introductionmentioning
confidence: 99%
“…Beside weaning, the neonatal period (from birth to post-natal day 28 in pigs), is also a key period in terms of intestinal development, with changes in epithelium morphology and gene expression with post-natal age [13], as well as ISC dynamics depending on gut location [14]. As opposed to weaning where the luminal environment does not seem to impact ISC, we recently demonstrated that changes in the luminal environment composition during the first week of life can imprint ISC, since organoids derived from the colon of antibiotic-treated vs. vehicle-treated piglets retained some, but not all, features of the changes observed in vivo at the epithelial level [15].…”
Section: Introductionmentioning
confidence: 99%